Detection of cervical neoplasia using measurement of Brn-3a in cervical smears with persistent minor abnormality. Issue 4 (1st June 2003) - Sindos, M.; Ndisang, D.; Pisal, N.; Chow, C.; Deery, A.; Singer, A.; Latchman, D.
Abstract : Measurement of the Brn-3a cellular transcription factor in cervical smears from women referred for colposcopy may improve the detection of underlying cervical neoplasia. In those women referred with persisting borderline or mildly dyskaryotic smears, those who had histologically proven underlying CIN II/III, had statistically significant higher Brn-3a levels than those with a similar smear but histologically shown to have HPV, CIN I, or no cervical abnormality. These results indicate that Brn-3a could play an important role in the near future in improving cervical cancer screening.